2016
DOI: 10.1242/dev.140129
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan 4 controls lymphatic vasculature remodeling during mouse embryonic development

Abstract: The role of fluid shear stress in vasculature development and remodeling is well appreciated. However, the mechanisms regulating these effects remain elusive. We show that abnormal flow sensing in lymphatic endothelial cells (LECs) caused by Sdc4 or Pecam1 deletion in mice results in impaired lymphatic vessel remodeling, including abnormal valve morphogenesis. Ablation of either gene leads to the formation of irregular, enlarged and excessively branched lymphatic vessels. In both cases, lymphatic valve-forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 29 publications
0
29
0
2
Order By: Relevance
“…Transmembrane (type I) heparan sulfate proteoglycan Syndecan-4 ( Sdc4 ) was shown to control LEC polarization via regulation of Vangl2 expression recently. Sdc4 deletion in mice results in abnormal valve morphogenesis (1123). Previously, it was reported that axon guidance genes semaphorin 3A ( Sema3a ), its receptors neuropilin-1 ( Nrp1 ), plexin A1 ( Plxna1 ) and ephrin B2 , a member of the Eph receptor tyrosine kinase family are required for lymphatic valve formation (72, 117, 501, 646).…”
Section: Development Of Lymphatic Vessel Networkmentioning
confidence: 99%
“…Transmembrane (type I) heparan sulfate proteoglycan Syndecan-4 ( Sdc4 ) was shown to control LEC polarization via regulation of Vangl2 expression recently. Sdc4 deletion in mice results in abnormal valve morphogenesis (1123). Previously, it was reported that axon guidance genes semaphorin 3A ( Sema3a ), its receptors neuropilin-1 ( Nrp1 ), plexin A1 ( Plxna1 ) and ephrin B2 , a member of the Eph receptor tyrosine kinase family are required for lymphatic valve formation (72, 117, 501, 646).…”
Section: Development Of Lymphatic Vessel Networkmentioning
confidence: 99%
“…Whether VEGFR2, VEGFR3 and VE-cadherin are necessary for flow response in LECs remains unknown. However, PECAM-1 was recently shown to act in parallel with syndecan-4 during mouse lymphatic vessel and LV morphogenesis ( Wang et al, 2016 ). The lymphatic vessels of Sdc4 −/− mice are hyperproliferative and hyperbranched, and the LV-forming endothelial cells do not reorient properly during the circumferential elongation process.…”
Section: Molecular Underpinnings Of Valve Development and Diseasementioning
confidence: 99%
“…This defect is due to the overexpression of planar cell polarity (PCP) protein VANGL2 in the cells with reduced syndecan-4. Knockdown of VANGL2 rescues the flow-induced alignment of LECs with reduced syndecan-4 ( Wang et al, 2016 ).…”
Section: Molecular Underpinnings Of Valve Development and Diseasementioning
confidence: 99%
“…It has previously been reported that syndecan-4 can initiate mechanochemical signalling without the need for other ECM receptors, exhibiting vinculin recruitment and activation of ERK 17 and PKC-α 18 . Syndecan-4 is also implicated in flow sensing in endothelial cells that ultimately confers atheroprotective effects 15,16 . We provide evidence that while syndecan-4 is capable of initiating mechanotransduction as a lone ECM receptor, the underlying signalling network integrates distinct plasma membrane receptors; EGFR which augments the mechanoresponse and β1 integrins which are required for adaptive cellular stiffening.…”
Section: Discussionmentioning
confidence: 99%
“…Syndecan-4 null mice exhibit delayed wound healing 7 , while syndecan-4 null cells show impaired contractility, cytoskeletal organisation, and immature focal adhesions [8][9][10][11][12] , all suggestive of mechanosensation deficits. Indeed, studies in endothelial cells under fluid shear have implicated syndecan-4 in mechanotransduction both in vitro 13,14 and in vivo 15,16 .…”
mentioning
confidence: 99%